Erratum: Complete sets of elastic, dielectric and piezoelectric properties of [001]-poled Pb (Zn1/3 Nb2/3) O3 -(6-7)% PbTiO3 single crystals of [110]-length cut (Applied Physics Letters (2008) 92 (212907)) - Shukla, R. (2014)
10.1063/1.3112562